Current and future use of angiotensin II receptor blockers in patients with COVID-19 - A. V. Matveev; V. A. Otdelenov; D. A. Sychev (Izdatelstvo OKI, 2020)
No scientific evidence for the negative influence of angiotensin II receptor blockers onto COVID-19 clinical course has been identified so far. Prescribing angiotensin II receptor blockers as COVID-19 pathogenetic therapy could only be considered within clinical trials. Patients who have been taking angiotensin II receptor blockers for approved indications should continue to do so.